The impact of types compensation system towards employee job performance: a case study of Tenaga Nasional Berhad (TNB), Banda Kaba Melaka / Nurul Shahiera Mohd Shah - Mohd Shah, Nurul Shahiera (2013)
Employee job performance is a process for establishing a shared workforce understanding about what is to be achieved at an organisation level. It focuses on aligning the organisational objectives and goal with the employees' skills, competency, development plans and the delivery of results. There are four objectives of doing this study. The first objective is to identify employee level of job performance among the employee based on employee’s perception. Seconds’ objective is to identify employee perception towards the level of effectiveness of compensation types that offer in TNB, thirds objective is to examine the relationship between compensation types and employee job performance in TNB, Banda Kaba Melaka and the last objectives is to identify the most influential types of compensation system that influence employees’ job performance. The study was conducted among 86 respondents of lower level employees in department of Melaka Barat, TNB, Banda Kaba Melaka. A descriptive research will be used as a researcher would like to understand the characteristics of the group in this study and distribution of questionnaire forms among employees in TNB. All statistical analysis from the organization will be carried out using the IBMSPSS Statistical Package version 20. For findings, the three determinants show that there are positive relationships between direct financial compensation, indirect financial compensation and non-financial compensation with employee job performance. From the findings also, it indicate that indirect financial compensation and non-financial compensation is the most influence factor for job performance in TNB, Banda Kaba Melaka. However, all this types of compensation system have a positive relationship with employee job performance.